Impact of National Innovation System on Digital Payment Systems in Mauritius - Ramgolam, Dayawati; Fuqiang, Zhao (American Journal of Business Science Philosophy, 2024)
The study examines how the National Innovation System (NIS) impacted the development and adoption of digital payment technologies in the country. This system played a vital role in promoting financial inclusion, enhancing operational efficiency, and supporting economic growth. The research evaluated the current landscape of digital payments in Mauritius, focusing on factors like infrastructure, adoption trends, and regulatory frameworks. A mixed-methods approach was used, blending quantitative data collection with qualitative policy analysis. Quantitative data was gathered through questionnaires, while qualitative insights were obtained from analyzing relevant policy documents. This dual approach allowed for a comprehensive assessment of key elements that influenced digital payment systems. The analysis explored various factors, including government regulations by investigating how the legal and regulatory environment shaped digital payment adoption; capacity for innovation by assessing the ability of the country's innovation ecosystem to support the growth of digital payment solutions; technological infrastructure by examining the availability of the technological resources necessary for digital transactions; socio-economic influences by analyzing how societal and economic conditions, such as income levels and access to technology, affected adoption rates; and competitive landscape by considering how competition among digital payment providers impacted innovation and service delivery. The study identified both opportunities and challenges within Mauritius' NIS, offering suggestions for improvements to foster greater digital payment adoption. The findings underscored the importance of nurturing a robust innovation ecosystem to drive digital transformation and economic development in emerging economies like Mauritius, highlighting how innovation could support wider access to financial services and contribute to national growth.
Keywords: innovation; digital payment; technology; economy; Mauritius